Evaluasi Penerapan Kebijakan e-SATRiA terhadap Peningkatan Penerimaan Pajak Daerah Kota Bandung - Haris Saeful Rohim; Etti Ernita Sembiring; Darya Setia Nugraha (Indonesian Accounting Research Journal, 2021)
This study aims to evaluate the implementation of the electronic-self assessment tax reporting application (e-SATRiA) policy at the Bandung City Regional Revenue Management Agency. The research method that the writer uses is qualitative research with data collection techniques by means of observation, interviews, and documentary studies or triangulation. The data analysis technique that the author uses in this study is the Miles and Huberman Model. The data source used in this research is primary data, namely from the results of interviews with BPPD Bandung city employees, while secondary data is obtained from the target data and the realization of regional tax revenues in the city of Bandung and the data obtained from the public satisfaction questionnaire on the e-SATRiA system. The results of this study indicate that the implementation of the e-SATRiA policy has been good, but the benefits have not been felt maximally because there are still policies that allow taxpayers to pay directly to the BPPD office of Bandung city.